2012
DOI: 10.1111/j.1475-2743.2012.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conservation agriculture on soil quality and productivity in contrasting agro‐ecological environments of Zimbabwe

Abstract: Experimentation by farmers with conservation agriculture (CA) is increasing in southern Africa, but local longer term data on these new production systems are scarce. This study focuses on CA research at two contrasting on‐farm sites and one on‐station long‐term trial in Zimbabwe. The on‐farm trials were conducted at Chikato village on a sandy soil at Zimuto Communal Area with low rainfall and at Hereford farm near Bindura on a clay‐rich soil in a high rainfall area. The on‐station trial was at Henderson Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 34 publications
13
112
1
Order By: Relevance
“…Similarly, studies conducted under the semi-arid conditions of Zimbabwe showed that over time CA practices improved hydraulic properties (unsaturated hydraulic conductivity and capillary sorptivity) of a clay loam soil 65 . However, studies also showed that the effect of CA on water infiltration was dependent on soil type, with the potential negative effect of waterlogging on granitic sandy soils, which have a tendency to accumulate too much water 23,30 . Water balance studies over a 5-year period (1994/5-1998/9) on clay soils at Hatcliffe, Zimbabwe by Nyagumbo 59 , allowed water losses through runoff and evapotranspiration to be compared between a CA system in the form of mulch ripping (MR) and conventional moldboard plowing (CMP) (Fig.…”
Section: Monocroppingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies conducted under the semi-arid conditions of Zimbabwe showed that over time CA practices improved hydraulic properties (unsaturated hydraulic conductivity and capillary sorptivity) of a clay loam soil 65 . However, studies also showed that the effect of CA on water infiltration was dependent on soil type, with the potential negative effect of waterlogging on granitic sandy soils, which have a tendency to accumulate too much water 23,30 . Water balance studies over a 5-year period (1994/5-1998/9) on clay soils at Hatcliffe, Zimbabwe by Nyagumbo 59 , allowed water losses through runoff and evapotranspiration to be compared between a CA system in the form of mulch ripping (MR) and conventional moldboard plowing (CMP) (Fig.…”
Section: Monocroppingmentioning
confidence: 99%
“…However, there are also conflicting results from the region 28 and elsewhere 29 that show no causal relationship between intensive tillage and carbon loss. Limited retention of surface crop residues adds to the decline in soil carbon in conventional systems 30 . Furthermore, accelerated soil erosion in tilled systems decreases the amount of important plant nutrients (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Following the division of 2nd grade areas, Deqing County, in the region with mid-subtropical hilly red soil, is mainly influenced by water erosion. The revised universal soil loss equation (RUSLE) [46][47][48] takes comprehensive account of rainfall, slope, vegetation, soil texture and human disturbance and estimates the average level of annual soil erosion through quantifying these five factors as rainfall erosivity (R), soil erodibility (K), topography (slope length and gradient LS), vegetation coverage factor (C) and water and soil conservation measures (P).…”
Section: The Valuation Of Soil Conservationmentioning
confidence: 99%
“…Thus, all measurement methods collected during the survey (LT and M1 to M5) refer to the same time as remote sensing measurements. Following the contribution of van Deventer et al (1997), the NDTI was calculated using the formula:…”
Section: Remote Sensing Analysismentioning
confidence: 99%
“…In order to achieve increases in agricultural productivity, a better and more sustainable use of land is advocated (sustainable intensification) by proponents of conservation agriculture. Thus, conservation agriculture has received considerable attention among scholars and policy makers (Kassam et al 2009;Erenstein et al 2012;Thierfelder and Wall 2012;Tesfaye et al 2015). The CGIAR-a global partnership on international agriculture research-has invested significantly into conservation agriculture research over the last decades (Renkow and Byerlee 2010) and a growing number of development organizations have been promoting conservation agriculture, with recent efforts focusing on smallholder farming systems in sub-Saharan Africa and Asia (Stevenson et al 2014).…”
Section: Introductionmentioning
confidence: 99%